A study of instrumental and intergrative motivations as factors influencing UTAR third year Chinese undergraduates in learning ESL - Wong, Yin Mun (2011)
It is undoubtedly that motivation appears as one of the most vital elements in the education field, especially in the matter of second language learning. The issue regarding which motivation (either instrumental or integrative) has greater influence among university students has been debated since centuries ago; also, numerous researches concerning this topic have been conducted all over the globe over the past decades as well. In this study, the researcher tends to find out the type of motivation which plays a more important role among Chinese university undergraduates in their second language learning process. The basis of the analysis is survey data and interviews responses collected from 50 university undergraduates as well as 2 lecturers. In this research, the introduction and background of the study are first discussed; subsequently, the methodology, findings as well as the analysis or discussions of results are presented in the final part of this research paper. The main findings of this study is that instrumental motivation appears to be more important among these students in learning a second language, compared to integrative motivation.